Highly sensitive temperature sensing probe based on two cascaded Fabry–Perot interferometers and Vernier effect. Issue 2 (23rd November 2022) - Zhu, Xiping; Jiang, Chao; Chen, Hailin; Huang, Huiling; Sun, Simei
Abstract: In this paper, a temperature sensing probe is designed using two cascaded Fabry‐Perot interferometers (FPIs). FPI1 is made by splicing single‐mode optical fiber (SMF)‐no‐core optical fiber‐capillary‐SMF in turn, and then drilling a micro‐hole on the capillary wall of FPI1 with femtosecond laser, and injecting dimethyl silicone oil (DSO) into the capillary through the micro‐hole with immersion method. FPI2 is made by splicing SMF‐capillary‐SMF sequentially. Due to the thermal sensitivity of DSO, the temperature sensitivity of a single FPI1 reaches −0.3674 nm/°C. When the free spectral ranges of FPI1 and FPI2 are close, their cascaded sensor will produce a Vernier effect for improving the sensitivity. The experimental results show that the sensitivity of the sensing probe is as high as 1.8456 nm/°C. In addition, the sensor has a compact structure and can be used flexibly in confined space temperature measurement.